Data for compositional analysis of moose - Courbin, Nicolas; Fortin, Daniel; Dussault, Christian; Courtois, R. (Dryad Digital Repository, 2014)
Data used to characterize the land cover type of node of network for moose. Used proportions of various land cover types are estimated based on the observed GPS locations. Available proportions of various land cover types are calculated based on the 100% minimum convex polygon.